Library management 101 : a practical guide - Hussey, Lisa K.; Velasquez, Diane (ALA Editions, 2019)
Just because a set of responsibilities isn't formally called management doesn't mean that it isn't management. And this vital text speaks to a reality that all current professionals already know: that is, everyone studying to enter the profession needs an introduction to the topic of management. Because no matter what one's role in an academic or public library context, it will involve decision-making, planning, and organization skills.